Change required: Chinese Businesses in Singapore - Singapore Management University (Institutional Knowledge at Singapore Management University, 2012)
Today, Chinese businesses play an important role in Singapore’s economy. They make up 99.3 per cent of all small and medium enterprises (SMEs) and employ 51 per cent of workers in the country, contributing 40 per cent of value add to the economy. However, the world economy has become more competitive and Chinese businesses in Singapore have been forced to look at modernizing and changing the way they do business.